Ethics, morality, and game theory - Mark Alfano; Hannes Rusch; Matthias Uhl (Games, 2018)
Ethics is a field in which the gap between words and actions looms large. Game theory and the empirical methods it inspires look at behavior instead of the lip service people sometimes pay to norms. We believe that this special issue comprises several illustrations of the fruitful application of this approach to ethics.
Keywords: 330; morals; ethics; strategic interaction; game theory; behavior; economics; philosophy